The paediatrician workforce and its role in addressing neonatal, child and adolescent healthcare in Kenya - English, M; Strachan, B; Esamai, F; Ngwiri, T; Warfa, O; Mburugu, P; Nalwa, G; Gitaka, J; Ngugi, J; Zhao, Y; Ouma, P; Were, F (BMJ, 2020)
Objective: To examine the availability of paediatricians in Kenya and plans for their development.